Scenariusz filmowy jako inspiracja - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Screenplay is a multifunctional project written by screenwriter or screenwriters for preparing next phases of film production. Changing and many times transformed forms of screenplay belong to the nature of screenwriting. Literary vision of film changes several times being result of synergy and typical work in progress: from general idea and high concept, through story, treatment, scalette, first draft and certain number of drafts, to final draft, director’s draft and shooting script. Marek Hendrykowski’s study describes and explains these terms as forms of literary film creation in three complementary aspects: creative re-vision, rewriting and remodeling.